Protect Others to Protect Myself: A Weakness of Western Countries in the Face of Current and Future Pandemics? Psychological and Neuroscientific Perspectives - Mermillod, Martial; Morisseau, Tiffany (Frontiers in Integrative Neuroscience, 2021)
The COVID-19 pandemic has generated a large number of publications in medicine and biology concerning the virus and the treatments, as well as in psychology, social sciences, and data sciences concerning the spreading of the virus. Surprisingly, much less articles have been published in neurosciences on this field of research and one can wonder whether cognitive neurosciences have anything to say at all on this hot topic. In this article, we highlight a perspective of research concerning differences in the individual perception of the pandemic in Western compared to Eastern countries. Although this problem is complex and multifaceted, including many other social variables, we suggest that cognitive neurosciences do have important and fundamental insights to provide concerning the collective response observed within these populations. More precisely, we propose the hypothesis that differences in the propensity to adopt a holistic perception of contamination processes at the group level, involving brain structures that are also associated with perspective taking and empathy, in particular the medial prefrontal cortex (MPFC) and the anterior cingulate cortex (ACC), could contribute to explain the differences in virus diffusion observed between Western and Eastern countries.